Reactive DC Magnetron Sputtering-Induced the Formation of Amorphous CuN Films Embedded Nanocrystalline WC Phase - Lin, Yue; Zhang, Shihong (Journal of Coating Science and Technology, 2016)
A novel amorphous CuN/nanocrystal WC (nc-WC/a-CuN) film synthesized by reactive dc magnetron sputtering is reported in this paper. The nc-WC/a-CuN42 at.% film which is composed of many WC dendrite crystals of 5~10 nm with (001) orientation embedded in amorphous CuN possesses ~55 GPa hardness. The high-temperature wear analysis shows that this novel film possesses the comparable excellent friction performance with DLC film which is attributed to self-lubricant function of a-CuN; simultaneously the film was still maintaining the higher hardness at elevated temperature.